Christian doctrine eight lectures delivered in the University of Cambridge to undergraduates of all faculties - Whale, J.S. (Glasgow, Scotland Collins, 1957)
Includes bibliographical references and index
First published 1941 by Cambridge UP
Keywords: Theology, doctrinal